The use of AI-powered writing tools in EFL academic writing in Indonesia: A meta-synthesis review - Yeni Savitri; Lusi Nurhayati; Sari Hidayati (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
In the context of globalized education, proficiency in standardized English writing is essential. However, many students encounter challenges, such as native language interference, inadequate linguistic proficiency, and negative perceptions of writing. This paper delves into AI writing tools, including Large Language Models, Digital Writing Assistants, Automated Paraphrasing Tools, and Machine Translators. This study provides a systematic review of qualitative research exploring the use of AI-powered writing tools in academic writing within the Indonesian context. Fifteen studies that matched the inclusion criteria were included. Qualitative data were extracted, analysed, and aggregated using meta-synthesis. To analyze data, the researcher employed thematic analysis. The synthesis reveals that existing research reported favorable perceptions of AI writing tools among teachers and students. They acknowledged positive impacts of the tools on the writing process and outcomes through the support of real-time feedback. Nevertheless, concerns about overreliance and academic integrity were notable. In terms of impact, the reviewed research indicated that these tools assisted students in improving their writing skills, enhancing the overall writing quality, and boosting writing confidence. This review concludes with recommendations for AI literacy training and institutional guidance to achieve effective integration. The findings further enrich the current discussion on the transformative role of AI tools in EFL academic writing and its implications for educational policy and practice.